Biotechnological Approaches for Host Plant Resistance to Insect Pests - Kumari, Pritam; Jasrotia, Poonam; Kumar, Deepak; Kashyap, Prem Lal; Kumar, Satish; Mishra, Chandra Nath; Kumar, Sudheer; Singh, Gyanendra Pratap (Frontiers in Genetics, 2022)
Billions of dollars are spent worldwide on insect control in agriculture every year. Until recently, broad-spectrum chemical insecticides were considered as the primary agents for agricultural pest control. However, over the years, the overreliance on pesticides has led to various negative impacts, such as the reduced population of beneficial insects, pesticide-resistant insects, and harmful effects on humans and the environment. There is an urgent need for the development of alternative measures or strategies for pest management aiming for minimum use of pesticides and conservation of natural enemies for maintaining a sustainable environment. As host plant resistance plays a vital role in integrated pest management but the development of insect-resistant varieties through conventional host plant resistance takes time, and is challenging as it involves many quantitative traits positioned at various loci. Therefore, recently biotechnological approaches have opened a new era of opportunities for insect control options. This will potentially provide a much larger array of novel insecticidal genes that are otherwise beyond the scope of conventional breeding. Biotechnological interventions can change the level and pattern of expression of genes and the development of transgenic varieties with insecticidal genes and can improve pest management by providing access to novel molecules. This review will discuss the emerging biotechnological tools available to develop insect-resistant engineered crop genotypes with a better ability to resist the attack of insect pests.